Економіко-екологічний вектор розвитку сучасного військово-промислового комплексу - Купінець, Л.Є.; Обнявко, Т.С. (Економічні інновації, 2014)
Визначено сутність та структуру військово-промислового комплексу України. Проведені дослідження сучасного стану військово-промислового комплексу України, проаналізовано його сильні та слабкі сторони. Запропоновано основні напрямки розвитку ВПК у межах концепції сталого розвитку. The essence and structure of Military-industrial complex (MIC) of Ukraine have been determined. Researches of the modern state of Ukraine’s military and industrial complex are conducted, strong and weak sides and also the most prespective possibilities of MIC are analysed. Basic directions of Ukraine's military industrial complex development within the stable development conception are offered.